Leadership Synergy And Collaboration In Advanced Inclusive Early Childhood Islamic Education - Maryani; Wibowo, Adi; Mua’arifah, Nurvianna; Handayani, Oktaviana Nur (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Inclusive education has become a global priority in promoting equal access to quality learning for all children, including those with special needs. In the context of Islamic-based Early Childhood Education (PAUD) in Indonesia, the implementation of inclusive practices remains a complex challenge that requires strong leadership and effective institutional management. This study aims to analyze the management strategies employed by RA Kuntum Kusuma Ani Yudhoyono in strengthening inclusive education within an Islamic early childhood institution. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews with principals, teachers, parents, and special education assistants, as well as documentation analysis. The data were analyzed thematically through stages of reduction, presentation, and interpretation following Miles and Huberman’s model. The findings reveal five key managerial aspects influencing the success of inclusive education: transformational and visionary leadership, continuous teacher training, active parental and community engagement, adaptive infrastructure, and an inclusive school culture grounded in empathy and diversity. These elements form an integrated system that aligns pedagogical inclusivity with spiritual and cultural values. The study contributes to the theory of inclusive educational management by presenting a contextual model that integrates leadership, teacher empowerment, and community partnership within a faith-based framework. Practically, it provides insights for Islamic early childhood institutions in developing sustainable and locally relevant inclusive practices. Further research involving multiple institutions is recommended to explore variations in leadership styles and inclusion models across different cultural contexts.